From Cash to Digital Wallet: Measuring Financial Inclusion in Manggarai, East Nusa Tenggara - Bahiyyah, Khariidatul (Politeknik Siber Cerdika Internasional, 2025)
This study aimed to measure the level of financial inclusion and analyze the transition process from cash to digital wallets in the Manggarai district, East Nusa Tenggara province, Indonesia. This study is an applied study in terms of purpose and a descriptive-survey study in terms of data collection method. The statistical population of this study comprised all adult residents of the Manggarai district, out of which 400 people were selected as a sample using the multi-stage cluster sampling method. Data were collected through a researcher-made questionnaire whose validity and reliability were confirmed and analyzed using descriptive and inferential statistics. The findings revealed that while 53.8% of respondents use a digital wallet, only 11.3% use it exclusively, while 42.5% were in a mixed mode, meaning they use both cash and digital transactions together. Significant generational disparity was observed in the adoption of financial technology: 84% of the elderly used only cash. Transaction speed ranked first, at 39.5%, and access to government subsidies followed with 36.3%. Major reasons for not adopting digital wallets included a lack of trust, 62.9%, and inadequate internet access, 56.7%. Results from this study can be useful to financial policymakers, digital payment service providers, and regional development planners in devising appropriate strategies to help accelerate financial transition.